2021
DOI: 10.1186/s12882-021-02415-w
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ischemic stroke and intracranial hemorrhage in patients with nephrotic syndrome

Abstract: Background The incidence of cerebral stroke, including ischemic infarction and intracranial hemorrhage (ICH), increases in patients with nephrotic syndrome (NS). However, the clinical characteristics of patients with NS and stroke remain elusive. We aimed to investigate the clinical presentation and prognosis among patients with NS and ischemic stroke (IS) or ICH. Methods We conducted a population-based retrospective cohort study of patients with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition, disease‐specific registries (Stroke, 21,23 Primary aldosteronism, 18,79 and Tuberculosis 31 ) and electronic medical record systems in major hospital systems that provide comprehensive services (ambulatory care, pharmacy, emergency services and inpatient care), 80,81 although not entirely population‐based, are useful data sources for this purpose as well. Detailed description of medical records review mechanism has been described for the Chang Gung Research Database 41,82 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, disease‐specific registries (Stroke, 21,23 Primary aldosteronism, 18,79 and Tuberculosis 31 ) and electronic medical record systems in major hospital systems that provide comprehensive services (ambulatory care, pharmacy, emergency services and inpatient care), 80,81 although not entirely population‐based, are useful data sources for this purpose as well. Detailed description of medical records review mechanism has been described for the Chang Gung Research Database 41,82 …”
Section: Discussionmentioning
confidence: 99%
“…Detailed description of medical records review mechanism has been described for the Chang Gung Research Database. 41,82 In reviewing pharmacoepidemiology articles from Taiwan and personal communications with investigators, we are aware that validations of diagnosis codes have been conducted in convenience samples of subjects, but the findings have not been reported separately. With these validation findings embedded in articles for which the main findings were association between certain drug exposures and outcomes, literature search through keywords related to validation may not accurately identify all potential articles.…”
Section: Usingmentioning
confidence: 99%
“…Previous studies showed similar results. 60,61 Stroke is one of the primary causes of morbidity and mortality in Malaysia, as it is in many other countries. With the growing proportion of elderly in the population and recent advancements in stroke prevention and treatment, the epidemiology of stroke is changing with time.…”
Section: Discussionmentioning
confidence: 99%